Thermal, environmental and economic analysis of a new thermoelectric cogeneration system coupled with a diesel electricity generator - Karana D.R.; Sahoo R.R. (My University, 2025)
In the current study, a domestic diesel electricity generator based new thermoelectric cogeneration system is studied with a 20% blend of mahua biodiesel fuel. The exhaust of the engine is considered as the heat source with the rectangular configuration geometry of the exhaust pipe, for heating water and producing electricity using thermoelectric generators. A thermal resistance model is developed for five cases at different positions for thermoelectric generators. The comparative study revealed that in Case 5, the maximum power of 35 W is obtained in which the TEGs are assembled with the inner wall of the rectangular exhaust configuration near to the heat source. However, the heat recovery unit could produce water temperatures up to 93°C. Furthermore, evaluation of the payback period and savings in cost by operating the cogeneration system has been done for all considered configurations of TEG based cogeneration systems. The theoretical analysis revealed that out of all the considered Cases, Case-5, TEGs near to the heat source, provides the best balance between the power and initial cost at sufficient water temperature. Furthermore, the study extends to the environmental impact of the cogeneration systems for the estimations of the CO2 saved by the waste heat. © 2020 Elsevier Ltd